Epigenetics and its implications for plant biology. 1. The epigenetic network in plants. - Grant-Downton, RT; Dickinson, H (2005)
BACKGROUND: Epigenetics has rapidly evolved in the past decade to form an exciting new branch of biology. In modern terms, 'epigenetics' studies molecular pathways regulating how the genes are packaged in the chromosome and expressed, with effects that are heritable between cell divisions and even across generations. CONTEXT: Epigenetic mechanisms often conflict with Mendelian models of genetics, and many components of the epigenetic systems in plants appeared anomalous. However, it is now clear that these systems govern how the entire genome operates and evolves. SCOPE: In the first part of a two-part review, how epigenetic systems in plants were elucidated is addressed. Also there is a discussion on how the different components of the epigenetic system--regulating DNA methylation, histones and their post-translational modification, and pathways recognizing aberrant transcripts--may work together.